Starch-Chitosan based Composite Edible Antimicrobial Film: Modelling the Growth of Selected Food Spoilage Microbiota - Panjagari, Narender Raju (Indian Journal of Dairy Science, 2015)
Antimicrobial packaging is one of the most promising active packaging systems that have been found highly effective in killing or inhibiting spoilage and pathogenic microorganisms that contaminate foods. The main cause of spoilage of many foods is microbial growth on the product surface mainly caused by psychrotrophs, Gram-negative and Gram-positive bacteria, yeasts and molds. In the present study, corn starch and chitosan based antimicrobial edible composite film was developed and its antimicrobial efficacy against Saccharomyces cerevisiae (NCDC-186), Aspergillus flavus (NCDC-268) and Lactobacillus acidophilus (NCDC-14) has been studied. Further, the growth characteristics of these organisms have been modelled. The thickness of the composite edible film was found to be 206.25 microns. The colour values indicated that the composite film had a lightness value (L*) of 22.36, redness or greenness value (a*) of -0.12 and yellowness or blueness value (b*) of -0.23. the optical density of starch-chitosan film composite film increased after 8 hours of exposure compared to native starch film (control) indicating rapid release of chitosan. The predicted maximum specific growth rate (Î¼max) of S. cerevisiae, A. flavus, and L. acidophilus in presence and absence of composite film were found to be 0.16 and 0.30, 0.13 and 0.43, and 0.21 and 0.32, respectively.